New species of Macrotomoderus Pic (Coleoptera: Anthicidae) from Southern China - Zhao, Yuchen; Wang, Xinpu (Zootaxa, 2025)
Seven new species of the genus Macrotomoderus Pic, 1901 from China are described: M. baoyui sp. nov. (Anhui), M. insolitus sp. nov. (Chongqing), M. jiangrixini sp. nov. (Hainan), M. jinyunshan sp. nov. (Chongqing), M. nanling sp. nov. (Guangdong), M. yintiaoling sp. nov. (Chongqing) and M. yuexiensis sp. nov. (Anhui). Images and diagnosis of new species are provided.